HIV-1 signalling remodels nuclear pores to licence infection - Dejan Mesner; Matthew V. X. Whelan; Maitreyi Shivkumar; Ann-Kathrin Reuschl; Riccardo Zenezini Chiozzi; Konstantinos Thalassinos; Robertus A. M. de Bruin; Clare Jolly (Nature, 2026)
Abstract HIV-1 is readily detected in resting CD4 + T cells in vivo 1–4 . However, resting T cells are highly refractory to cell-free virus infection in vitro 5–7 and require mitogenic activation to become permissive. This paradox raises the fundamental question of what makes a T cell permissive for HIV-1. Here we address this and show that HIV-1 capsid nuclear import at the nuclear pore complex (NPC) is a bottleneck to resting T cell infection, but that HIV-1 overcomes this by triggering receptor-mediated signalling during cell–cell spread to drive nuclear import and licence infection. Coupling viral and cellular assays with super-resolution imaging, we show that contact between HIV-1 infected and uninfected T cells triggers CD4–LCK signalling that activates CDK1, independent of cell-cycle entry, phosphorylating nucleoporins and priming the NPC to promote HIV-1 nuclear import. Critically, cell–cell contact also accelerates nuclear import in activated T cells, providing a paradigm for why cell–cell spread dominates infection. By contrast, HIV-1 virions do not trigger this response, explaining why resting T cells cannot be efficiently infected by cell-free virus. We propose that HIV-1 has evolved to selectively activate CD4 signalling during cell–cell spread to regulate infection at the step of the NPC, offering an explanation for how resting T cells can be infected in vivo.